Collaborative production of informational goods under Hackathon Methodology. Transformations on collaborative production: expectations and goals of social agents - Maioli, Dr. Esteban (IJRDO - Journal of Business Management, 2017)
During the last years, events known as "hackatones" have been generalized. The term is composed by the words "marathon" and "hack". These are events in which a diverse set of social actors (most of them programmers, graphic designers and others) gather in a common physical space for the development of software applications (or apps) as collaborative production (Bortz 2013). The duration of these events is relatively short (between one and three days, approximately) and generally includes the inclusion of incentives (of different type and significance) for teams that are formed ad hoc in the scope of hackathonThis mode of production of informational goods (Cafassi, 1998) has gained relevance within the contemporary phase of development of the capitalist mode of production known as informational capitalism (Zukerfeld, 2010). The production of this type of goods in these events refers to a specific mode of realization outside of the traditional bureaucratic structures of the companies (Bauwens, 2006), which are enabled to a large extent by the breadth of the exchange capacities, discussion and dissemination because of the generalization of the Internet. This article intends to review these working methodologies, to identify tensions, continuities and ruptures in the "horizontal" production that these processes imply, as well as research the consequences on human resources that these strategies imply.